MyMapper: plataforma de mapeamento de ambientes 3D - Franczak, Douglas Diogo (2015)
In robotics the area where it's studied the techniques of mapping and localization is called SLAM, this area aims to develop more precise methods of mapping and localization, because one of the more common problems in SLAM is the deformation or imperfection of the maps when it's necessary locate itself on those maps. The objective of this project is to create a SLAM system focusing on the integration of data coming from orientation sensors aiming to realize a sweep of the environment to create a map. Another focus of this project is in the method that the data is integrate and in the choice of the components, because both the methods and the mechanical construction needs to have some didactic value. This document will demonstrate, the mechanical construction of the platform; the interpretation of the data coming from the sensors: accelerometer, gyroscope and infrared rangefinder; the integration of the data from accelerometer and gyroscope starting from the complementary filter and the reconstruction of this data on a 3D environment. The LabVIEW is a software for visual programming that has been chosen because it's used a lot on modern industry. The myRio is used as a data collector because it is programmed on LabVIEW and it has a variety of functionalities that are very useful for this project, and also it's made specifically to be didactic. The Unity Engine is a software for game creation, which is easier to recreate 3D environments because of its popularity, which means that there's a bigger support, and because of the possibility of utilizing visual programming on certain aspects of the system in conjunct with the traditional C# programming. The MyMapper has been constructed in way that it has a simple interface, providing to the user all the necessary options for calibration and maintaining a clean and modular code, to facilitate future improvements. In the end, the MyMapper can map the environment of a meter, maximum, the limit in which the telemeter can work, but the details of this environment are deformed for various motives, depending on the calibration of the system. Even so, the system can be used to detect obstacles, because the deformations are small and modify only the format of the piece and not its general position.